Features of expression of protein Claudin 11 at various forms of male infertility - Bazalytska, S. V.; Romanenko, A.M.; Persidsky, Yu. V. (Pathologia, 2013)
Immunohistochemical features of an expression of protein Claudin 11 in testicular tissue of 28 patients with excretory-obstructive and secretory forms of male infertility are studied. Significant decrease of protein Claudin 11 IHC expression level at the secretory form of male infertility and at syndrome «only Sertoli cells» is revealed in comparison with excretory-obstructive form of male infertility. Results testify to considerable disturbances of blood-testis barrier, which have become the basis of the development of additional immune component and intensification of pathological changes in patients with the secretory form of male infertility.